Evaluation of Risk Factors and Histopathological Patterns in Abnormal Uterine Bleeding: A Retrospective Study from Benghazi - Manal Yaya; Ghazala Abouzrig; Sumeia Ghannay; Anas Khalifah; Salah Altarigi; Latifa Shallouf; Halima Mohammed (AlQalam Journal of Medical and Applied Sciences, 2026)
Abnormal uterine bleeding (AUB) is a common gynecological complaint that affects women of reproductive age and often requires thorough clinical and histopathological evaluation. This retrospective study analyzed the records of 299 female patients admitted to the Gynecology Department at Benghazi Medical Center between January 2021 and December 2024, all were presented with vaginal bleeding and diagnosed with AUB. Demographic data, clinical symptoms, and histopathological diagnoses were reviewed and analyzed. The average patient age was 26.7 years, with 91% under the age of 40. Most participants were from Benghazi (82%), married (91%), and nulliparous (87%). A large majority (87%) had no history of breastfeeding. The most frequently reported symptoms were irregular menstrual bleeding (50.5%) and spotting (39.13%). Less common complaints included postmenopausal bleeding, severe cramps, blood clots, moderate bleeding, and premenopausal bleeding. Histopathological findings were predominantly benign (68%), followed by endometrial polyps (12%), hyperplasia (6%), adenomyosis (5%), and endometrial carcinoma (4%). A statistically significant relationship was found between presenting symptoms and histopathological outcomes. Irregular cycles and spotting were most linked to benign conditions. In conclusion, AUB in this cohort was most common among young, married, nulliparous women with limited breastfeeding history. Benign causes were the predominant diagnosis, and malignancy was rare. The findings underscore the importance of early clinical assessment and appropriate investigation to ensure effective management, particularly in reproductive-aged women, to minimize potential complications and improve outcomes.